Produksi Video Edukasi Antigratifikasi: Sebuah Kolaborasi Pengabdian Kepada Masyarakat Antara Universitas dengan Lembaga Negara - Petrus Damiami Sitepu; Sita Dewi; Wida Kurnianda Djamil; Ari Dina Krestiawan; Ignatius Krismawan (Abdimas Universal, 2024)
Universitas Multimedia Nusantara’s Film and Digital Journalism programs and Corruption Eradication Commission (KPK) collaborated to produce five documentary movies on anti-corruption as part of a community service program. The production of the documentary movies was funded by the KPK, which aims to use the documentary in their anti-corruption campaigns. We chose the documentary format to emphasize data and facts. The documentaries feature civil servants in different cities across Indonesia, who have received awards or acknowledgment for their anti-corruption commitment and efforts in their respective organizations. They are Rifqi Abdilah (Probolinggo, East Java), Budi Ali Hidayat (Cimahi, West Java), Achmad Nasution (Boyolali, Central Java), Badrul (Sumenep, East Java) and Musdalipa (Pangkajene Islands, South Sulawesi). This documentary uses a strong film approach, with elements of narrative and film style in audio and visual elements. The production of this documentary film uses the stages of documentary film production, namely research, pre-production, production, post-production, exhibition, and film distribution. The KPK will screen the documentary movies in their anti-corruption campaign events across the country.